Arabidopsis thaliana—Myzus persicae interaction: shaping the understanding of plant defense against phloem-feeding aphids - Louis, Joe; Shah, Jyoti (Frontiers in Plant Science, 2013)
The phloem provides a unique niche for several organisms. Aphids are a large group of Hemipteran insects that utilize stylets present in their mouthparts to pierce sieve elements and drink large volumes of phloem sap. In addition, many aphids also vector viral diseases. Myzus persicae, commonly known as the green peach aphid (GPA), is an important pest of a large variety of plants that includes Arabidopsis thaliana. This review summarizes recent studies that have exploited the compatible interaction between Arabidopsis and GPA to understand the molecular and physiological mechanisms utilized by plants to control aphid infestation, as well as genes and mechanisms that contribute to susceptibility. In addition, recent efforts to identify aphid-delivered elicitors of plant defenses and novel aphid salivary components that facilitate infestation are also discussed.